Spawning Red Lace Guppies (Poecilia reticulata) with Different Substrates - Kasprijo Kasprijo; Rudy Wijaya; Syafiq Nur Arifin; Intan Adelia; Via Angellica Santoso; Alvis Safinatun Najah; Eka Ayu Setiawan; Farah Rakhmatika; Lintang Cyan Nugraheni; Andri Maulana Rizki (Indo Journal of Multidisciplinary Science, 2025)
The red lace guppy (Poecilia reticulata) is a highly adaptable fish species with a high tolerance to a wide range of temperatures and salinity levels, even in polluted waters. This study aims to determine the spawning and maintenance methods for guppy (Poecilia reticulata) fry. This study used the RAL method with three treatments and two replications. P(1) plastic tank with a Malang sand base and aquatic plants (Hydrilla sp.), P(2) plastic tank with a Malang sand base without aquatic plants (Hydrilla sp.), P(3) plastic tank without a base and without aquatic plants (Hydrilla sp.). The plastic spawning and maintenance tanks were filled with approximately 20 cm of water and labeled according to the treatment and replication. Treatment 1, which included Malang sand and the aquatic plant Hydrilla sp., had the highest spawning success rate, yielding 67 fish. This was due to the addition of plant substrate for hiding places and the addition of Malang sand to stimulate the fish's body, which is received by receptors and transmitted to the nervous system.